Climate changes and their impacts on water resources in semiarid regions: a case study of the Wei River basin, China. Issue 26 (12th September 2012) - Zhao, Guangju; Mu, Xingmin; Tian, Peng; Wang, Fei; Gao, Peng
Abstract Understanding the impacts of climate change and human activity on the hydrological processes in river basins is important for maintaining ecosystem integrity and sustaining local economic development. The objective of this study was to evaluate the impact of climate variability and human activity on mean annual flow in the Wei River, the largest tributary of the Yellow River. The nonparametric Mann–Kendall test and wavelet transform were applied to detect the variations of hydrometeorological variables in the semiarid Wei River basin in the northwestern China. The identifications were based on streamflow records from 1958 to 2008 at four hydrological stations as well as precipitation and potential evapotranspiration (PET) data from 21 climate stations. A simple method based on Budyko curve was used to evaluate potential impacts of climate change and human activities on mean annual flow. The results show that annual streamflow decreased because of the reduced precipitation and increased PET at most stations. Both annual and seasonal precipitation and PET demonstrated mixed trends of decreasing and increasing, although significant trends (P < 0.05) were consistently detected in spring and autumn at most stations. Significant periodicities of 0.5 and 1 year (P < 0.05) were examined in all the time series. The spectrum of streamflow at the Huaxian station shows insignificant annual cycle during 1971–1975, 1986–1993 and 1996–2008, which is probably resulted from human activities. Climate variability greatly affected water resources in the Beiluo River, whereas human activities (including soil and water conservation, irrigation, reservoirs construction, etc.) accounted more for the changes of streamflow in the area near the Huaxian station during different periods. The results from this article can be used as a reference for water resources planning and management in the semiarid Wei River basin. Copyright © 2012 John Wiley & Sons, Ltd.